Increased Levels of TNF-α, IL-6, and IL-10 are Associated with The Degree of Liver Fibrosis in Chronic Hepatitis B Patients with NUC Therapy - Maimunah, Ummi; Kholili, Ulfa; Putra, Rheza Rahmadika; Brimantyo, Dio; Wirantara, Hendy (The Indonesian Biomedical Journal, 2024)
BACKGROUND: Liver fibrosis in chronic hepatitis B (CHB) involves the host immune responses mainly T-lymphocyte regulatory cells and cytokines production. Tumor necrosis factor (TNF)-α, interleukin (IL)-6, and IL-10 have been reported to play a crucial role in the development of liver fibrosis. However, their association with liver fibrosis in treated CHB patients remains unclear. Therefore, this study was conducted to investigate the association between TNF-α, IL-6, and IL-10 with the degree of liver fibrosis in treated CHB patients.METHODS: This was a cross-sectional prospective study including 101 treated chronic hepatitis B subjects. TNF-α, IL-6, and IL-10 serum levels were measured with quantitative sandwich enzyme-linked immunosorbent assay (ELISA) kit. Transient elastography result was classified according to METAVIR score. Data was analyzed by the Spearman correlation test with a p<0.05 was considered statistically significant.RESULTS: From 101 subjects, there were significant differences were seen in TNF-α, IL-6, and IL-10 between patients with mild, significant and advance fibrosis. TNF-α (r=0.292; p<0.05), IL-6 (r=0.221; p<0.05), and IL-10 (r=0.208; p<0.05) were significantly correlated with the degree of fibrosis. After multivariate analysis, TNF-α was the only one cytokine parameter which significantly correlated with the degree of fibrosis.CONCLUSION: Levels of TNF-α, IL-6 and IL-10 are associated with the degree of liver fibrosis. These parameters may potentially be used to evaluate the development of liver fibrosis in treated CHB patients.KEYWORDS: chronic hepatitis B, liver fibrosis, cytokines, transient elastography